Pengaruh Price Discount dan Pendapatan Terhadap Impulsive Buying Pada Online Shop (Studi Kasus Pada Tenaga Kependidikan Di Universitas Negeri Padang) - Muarti Muarti; Tri Kurniawati (Universitas Negeri Padang, 2023)
This study aims to determine the effect of price discount and income on impulsive buying behavior in online shops for education staff at Padang State University. This type of research is quantitative research with a causal associative approach. Samples were taken using the Cochran formula with 97 respondents and selected by purposive sampling technique. The type of data used in this study is primary data obtained from distributing questionnaires to education staff at Padang State University with the following criteria: 1) respondents are education staff at Padang State University who have shopped at online shops, 2) respondents have impulsive behavior buying in online shop. The analytical method used is multiple regression analysis using SPSS version 16. The results of this study indicate 1) price discount and income have a positive and significant effect on impulsive buying in online shops, seen from the sig value. 0.014<0.05. 2) price discount has a positive and significant effect on impulsive buying in online shops seen from the sig value of 0.004 <0.05. 3) income does not have a positive and significant effect on impulsive buying at the online shop as seen from the sig value of 0.764>0.0.